Patterns of Insulin Secretion During First-Phase Insulin Secretion in Normal Chinese Adults - Yuan, Tao; Song, Shuoning; Zhao, Tianyi; Duo, Yanbei; Wang, Shihan; Gao, Junxiang; Liu, Shixuan; Dong, Yingyue; Li, Rui; Fu, Yong; Zhao, Weigang (Frontiers in Endocrinology, 2021)
Abstract Background The increasing of diabetes worldwide is alarming. Decreased acute insulin response to intravenous glucose (IVGTT) during first-phase insulin secretion (FPIS) is a characteristic of diabetes. However, knowledge of the insulin secretion characteristics identified by different time to glucose peak in subjects with different metabolic state is sparse. Aims This study aimed to find different patterns of FPIS in subjects with normal glucose tolerance (NGT) and analyzed the relationship between insulin secretion patterns and the risk for development of type 2 diabetes mellitus (T2DM). Methods A total of 126 subjects were divided into three groups during a 10-min IVGTT, including NGT with time to glucose peak after 3 min (G1, n=21), NGT with time to glucose peak at 3 min (G2, n=95) and prediabetes or diabetes with time to glucose peak at 3 min (G3, n=10). Glucose, insulin and C-peptide concentrations at 0, 3, 5, 7 and 10 min during the IVGTT were tested. IVGTT-based indices were calculated to evaluate the insulin secretion and insulin sensitivity. Results Age, BMI, waist-to-hip ratio, TG and HbA1c of subjects were gradually higher while HDL-C was gradually lower from G1 to G3 (P for linear trend < 0.05) and the differences between G1 and G2 were also statistically significant (P < 0.05). Glucose peak of most participants in G1 converged at 5 min and the curves shape of insulin and C-peptide in G2 were the sharpest among three groups. There was no significant difference in all IVGTT-based indices between G1 and G2, but AUCIns, AUCIns/AUCGlu and △Ins3/△Glu3 in G2 were the highest and the P value for linear trend of those indices among three groups were statistically significant (P＜0.05). Conclusions Two patterns of FPIS were in subjects with NGT, while subjects with later time to glucose peak during FPIS might be less likely to develop T2DM in future.